Discovery Learning to Develop Student Reflective Thinking Ability and Self-Efficacy - Listyotami, Mega Kusuma; Noer, Sri Hastuti; Haenilah, Een Yayah (Al-Jabar: Jurnal Pendidikan Matematika, 2018)
The research and development aims to produce a discovery learning model that is oriented towards the student ability of reflective thinking and  self-efficacy. The research was conducted using the Research and Development (R and D) method. The research and development model used refers to the procedure of R and D development by Gall and Borg by Sukmadinata that is  ADDIE. The steps for implementing the research and development strategy include; (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. The Data collecting methods and instruments are used tests and non-tests. The Data collection techniques using observation, interviews, questionnaires, and tests. The Data analysis techniques used in research and development are quantitative and qualitative descriptive. The results showed that the discovery learning model that was oriented towards the student ability of reflective thinking and self-efficacy  was effective to improve the student ability of reflective thinking and self-efficacy  respectively by 77% and 30%.Keywords: Discovery Learning, Relative thinking, dan Self-Efficacy